2015
DOI: 10.1007/s00125-015-3751-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of insulin in the regulation of human skeletal muscle protein synthesis and breakdown: a systematic review and meta-analysis

Abstract: Aims/hypothesis We aimed to investigate the role of insulin in regulating human skeletal muscle metabolism in health and diabetes. Methods We conducted a systematic review and metaanalysis of published data that examined changes in skeletal muscle protein synthesis (MPS) and/or muscle protein breakdown (MPB) in response to insulin infusion. Random-effects models were used to calculate weighted mean differences (WMDs), 95% CIs and corresponding p values. Both MPS and MPB are reported in units of nmol (100 ml le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
137
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(144 citation statements)
references
References 55 publications
2
137
2
3
Order By: Relevance
“…Insulin is a vasodilatory factor and has the dual effect of enhancing muscle protein synthesis and inhibiting breakdown 73,74) . Insulin promotes net muscle protein anabolism primarily by inhibiting protein breakdown, rather than by stimulating protein synthesis 73,74) .…”
Section: Effect Of Blood Flow Volume On Skeletal Muscle Protein Metabmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin is a vasodilatory factor and has the dual effect of enhancing muscle protein synthesis and inhibiting breakdown 73,74) . Insulin promotes net muscle protein anabolism primarily by inhibiting protein breakdown, rather than by stimulating protein synthesis 73,74) .…”
Section: Effect Of Blood Flow Volume On Skeletal Muscle Protein Metabmentioning
confidence: 99%
“…Insulin is a vasodilatory factor and has the dual effect of enhancing muscle protein synthesis and inhibiting breakdown 73,74) . Insulin promotes net muscle protein anabolism primarily by inhibiting protein breakdown, rather than by stimulating protein synthesis 73,74) . In addition, insulin appears to have a permissive role in protein synthesis in the presence of elevated amino acid levels, and plays a clear role in reducing protein breakdown independent of amino acid availability 74) .…”
Section: Effect Of Blood Flow Volume On Skeletal Muscle Protein Metabmentioning
confidence: 99%
See 1 more Smart Citation
“…A later study (29) scrutinizing this issue reported that although whole body protein breakdown measured with leucine was similar after a 22-h fast in obese and lean women when calculated per LBM, muscle forearm leucine release per 100 ml of forearm tissue was dramatically (Ͼ50%) decreased in obese subjects and that AT accounted for up to 10% of whole body protein breakdown in both lean and obese subjects. It has been estimated that skeletal muscle contains between 30 and 45% of total body protein and contributes between 20 and 35% of whole body protein turnover (1). With fasting, it has been reported that up to 2 wk of starvation did not increase the leucine rate of appearance/protein breakdown in obese subjects, whereas 60 h of fasting resulted in higher leucine rates of appearance and oxidation rates in lean subjects (37).…”
mentioning
confidence: 99%
“…Testosterone is well known to increase muscle mass by increasing the rate of muscle protein synthesis partly via stimulating IGF‐1 expression (Mudali & Dobs, 2004). Insulin appears to play a crucial role in maintaining the rate of muscle protein synthesis and breakdown, both in health and disease (Abdulla, Smith, Atherton, & Idris, 2016). Although the exact mechanism is not fully understood, as a key anabolic hormone, insulin stimulates muscle growth via secreting IGF‐1 followed by activation of the PI3K and Akt (also known as protein kinase B) signaling pathways via mammalian target of rapamycin (mTOR) that controls protein synthesis and the forkhead box O (FOXO) that controls protein degradation.…”
Section: Introductionmentioning
confidence: 99%